Cardiac toxicity of fluoroquinolones and bedaquiline - G. N. Mozhokinа; A. G. Sаmoylovа (Туберкулез и болезни лёгких)
The review analyzes data on the impact of fluoroquinolones and bedaquiline on the cardiac conduction system. The dependence of the cardiotoxic effect of fluoroquinolones on their influence on the potassium channels of cardiomyocytes is presented. The article demonstrates the importance of concomitant factors (potassium level in the blood, concurrent heart disorders, a genetically determined amount of HERG receptors in the myocardium, concomitant drug therapy) in the development of the cardiac toxicity caused by fluoroquinolones and bedaquiline.